Abraham - Beckstrand, Jennifer (Beckstrand, Jennifer. Petersheim brothers., 2019)
With their house full to bursting since Mammi and Dawdi moved back in, the Petersheim twins know the only way to get their bedroom back is to get their older brothers married off. But Abraham is so shy, he<U+2019>ll barely speak to girls. Still, they<U+2019>ve noticed how he looks at Emma Wengerd at church. Emma is so talkative, Abraham<U+2019>s quiet ways wouldn<U+2019>t matter a bit. Soon, the boys have hatched a scheme that sends Abraham right to Emma<U+2019>s door<U+2014>and her chicken coop . . . Abraham doubts that pretty, popular Emma would be interested in him. Yet when he finds himself by her side, having to straighten out the twins<U+2019> mischief<U+2014>more than once<U+2014>he can<U+2019>t help imagining a future with her. And the more time they spend together, the more Abraham realizes that perhaps no matter how many boys buzz around Emma, with faith, it<U+2019>s only the right one that counts . . .